Protracted febrile myalgia syndrome in children with familial Mediterranean fever - systematic review and a case report - Hospach, Toni; Blankenburg, Friederike; Heinkele, Anita; von Kalle, Thekla; Uziel, Yosef; Kallinich, Tillmann; Rücklová, Kristina (Pediatric rheumatology online journal, 2024)
INTRODUCTION: Protracted febrile myalgia syndrome (PFMS) is a rare manifestation of familial Mediterranean fever (FMF), characterized by myalgia, fever and elevated inflammatory markers lasting several weeks. As the hallmark of FMF are short episodes of disease symptoms, the long duration of PFMS may lead to a delayed diagnosis and treatment. OBJECTIVES: 1. To perform a review of literature and rheumatology textbooks focused on clinical features and treatment of PFMS in children. 2. To present our own case. METHODS: All articles in Pub Med generated using the keywords "protracted febrile myalgia" and information on PFMS in seven rheumatology textbooks were collected. The systematic review was supplemented with our own case presentation. RESULTS: In total, 18 articles with 78 pediatric patients (including our own) were retrieved. More than half of the patients presented with PFMS as the first manifestation of FMF. All complained of myalgia, 65% of abdominal pain and 26% had a rash. Corticosteroids (CS) were effective in 77%. In all CS-refractory cases, anakinra was shown efficient. MRI was used in 5 patients and showed myositis in all of them. The scrutiny of seven rheumatology textbooks showed that PFMS presenting with myalgia was mentioned in six. Possible accompanying symptoms were described only once, the long duration of symptoms twice, the efficacy of corticosteroids three times and anakinra only once. The presented 6 year old patient manifested with fever, myalgia, abdominal pain and petechial rash lasting 6 weeks. She had undergone multiple diagnostic procedures before her parents mentioned a positive family history for FMF. The subsequent genetic testing confirmed a homozygosity for M694V pathogenic variant in the MEFV gene. CONCLUSION: The long duration of PFMS may be misleading to clinicians especially if PFMS occurs at manifestation of FMF. The fact that more than half of the reported patients experienced PFMS as the presenting symptom of FMF is one of the key findings of our study. Our case presentation demonstrates the importance of genetic testing early in suspected autoinflammatory diseases. Furthermore, MRI may be an important diagnostic tool showing myositis in PFMS.
Keywords: magnetická rezonanční tomografie; Fever; myalgie; Magnetic Resonance Imaging; Syndrome; syndrom; Humans; Familial Mediterranean Fever; horečka; familiární středomořská horečka; Myalgia; dítě; lidé; Child